Resolving a taxonomic enigma: Rediscovery of the Mindanao endemic Begonia sordidissima (Begoniaceae) after over a century confirms its distinct status from B. mindorensis - Naive, Mark Arcebal K.; Along, Archie A.; Rozano, Ralph Rj E.; Ruales, Jeco Jed J. (Phytotaxa, 2025)
Begonia sordidissima has been considered as a synonym of B. mindorensis since 1923. Our recent fieldwork led to the rediscovery of B. sordidissima in Mindanao after more than a century, prompting a detailed morphological study that confirms its reinstatement as a distinct species. We designate lectotypes for both names and provide an emended description, including new data on pistillate flowers, photographs, updated distribution information, habitat preference, and a preliminary IUCN conservation assessment. This work underscores the critical need for continued field exploration and taxonomic revision in biodiversity-rich yet threatened regions such as the Philippines.